Network Communications Technology - Elahi, Ata (Delmar, 2001)
Keywords: Computer networks; Data transmission systems; dept.csc; faculty_collection

Tracking remotely sensed cloud images in time and space - Daponte, John S; Vitale, Joseph N; Parikh, Jo Ann; Tselioudis, George (Proceedings of SPIE, 2001)
Temporal and spatial analysis was applied to a sequence of cloud top pressure (CTP) images and cloud optical thickness (TAU) images, and a storm tracking algorithm was proposed. A sequence of storm tracks from the satellite images was developed from the satellite images. Composite images were created by projecting ahead in time and substituting the first valid pixel for missing data, and a variety of CTP and TAU cut-off values were used to identify regions of interest. The region correspondences were determined from one time frame to another which yielded the storm center coordinates. The obtained tracks were compared to the storm tracks computed from sea level pressure data by matching the results first in time and then in spatial distance.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/054-660-919-588-122 tex.type: [object Object]
Keywords: Algorithms; Climatology; Cloud top pressures (CTP); Clouds; Correspondence problem; Data reduction; Image analysis; Mathematical models; Radar tracking; Remote sensing; Satellite images; Sea level; Storm tracks; Storms; Temporal and spatial analysis; Weather forecasting; Weather satellites; dept.csc